what solution matches 3i + 2i - 7 = 18

9 answers

To solve the equation \( 3i + 2i - 7 = 18 \), we start by simplifying the left side.

Combine the like terms (the terms with \( i \)):

\[ 3i + 2i = 5i \]

So the equation simplifies to:

\[ 5i - 7 = 18 \]

Next, we'll isolate \( 5i \) by adding 7 to both sides:

\[ 5i = 18 + 7 \]

This simplifies to:

\[ 5i = 25 \]

Now, divide both sides by 5 to solve for \( i \):

\[ i = \frac{25}{5} = 5 \]

Thus, the solution is:

\[ i = 5 \]

What solution matches 3i+5=2i-7

To solve the equation \( 3i + 5 = 2i - 7 \), we will isolate \( i \) by following these steps:

  1. Move the terms involving \( i \) to one side: Subtract \( 2i \) from both sides:

\[ 3i - 2i + 5 = -7 \]

  1. This simplifies to:

\[ i + 5 = -7 \]

  1. Isolate \( i \): Subtract \( 5 \) from both sides:

\[ i = -7 - 5 \]

  1. This simplifies to:

\[ i = -12 \]

Thus, the solution to the equation \( 3i + 5 = 2i - 7 \) is:

\[ i = -12 \]

What solutions matches 3i+5=3i+7

To solve the equation \( 3i + 5 = 3i + 7 \), we start by trying to isolate \( i \).

  1. First, subtract \( 3i \) from both sides:

\[ 3i + 5 - 3i = 3i + 7 - 3i \]

This simplifies to:

\[ 5 = 7 \]

  1. The statement \( 5 = 7 \) is a contradiction, meaning there are no values of \( i \) that can satisfy this equation.

Thus, the conclusion is that there is no solution to the equation \( 3i + 5 = 3i + 7 \).

What solution matches 3(2i+7)=6i+21

To solve the equation \( 3(2i + 7) = 6i + 21 \), we first simplify the left side:

  1. Distribute the 3 on the left side:

\[ 3(2i) + 3(7) = 6i + 21 \]

This simplifies to:

\[ 6i + 21 = 6i + 21 \]

  1. Now, we can see that both sides of the equation are identical:

\[ 6i + 21 = 6i + 21 \]

This means that the equation is true for all values of \( i \).

Thus, the solution is that there are infinitely many solutions, or we can say all values of \( i \) are solutions.

What solution matches 3(2i-7)=15

To solve the equation \( 3(2i - 7) = 15 \), follow these steps:

  1. Distribute the 3 on the left side:

\[ 3 \cdot 2i - 3 \cdot 7 = 15 \]

This simplifies to:

\[ 6i - 21 = 15 \]

  1. Isolate the term with \( i \) by adding 21 to both sides:

\[ 6i - 21 + 21 = 15 + 21 \]

This simplifies to:

\[ 6i = 36 \]

  1. Solve for \( i \) by dividing both sides by 6:

\[ i = \frac{36}{6} = 6 \]

Thus, the solution to the equation \( 3(2i - 7) = 15 \) is:

\[ i = 6 \]